Estudo dos mecanismos de compactação em misturas entre solo arenoso e altos teores de emulsão asfáltica - Lima, Fabiola Costa de (2019)
This paper presents an evaluation of the mechanisms which define the compaction of mixtures between sandy soil and high asphalt emulsion contents. A sandy soil classified according to the Unified Soil Classification System as SP and a cationic asphalt emulsion slow set (RL-1C) were used. The mixtures between soil and asphalt emulsion were manufactures with asphalt emulsion contents varying from 13% to 31%, in weight, and were compacted under different conditions, in order to allow the identification of the mechanisms responsible for their compaction, and compaction methodology suitable for this material. Results show that the mechanisms governing the compaction of mixtures between soil and high asphalt emulsion contents are significantly different from those ones regarding the granular and fine soils. The stiffness of the residual asphalt binder on the soil particles presents itself as the most important factor that has influenced the compaction of the studied mixtures, indicating that to obtain an efficient compaction of the mixtures it is necessary to increase the energy used in the compaction process or decreasing the viscosity of the residual binder by heating during the compaction procedure.